2020
DOI: 10.21203/rs.3.rs-47972/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adverse events of video capsule endoscopy over the past two decades: a systematic review and proportion meta-analysis

Abstract: Background: A full spectrum of video capsule endoscopy (VCE) adverse events over the past two decades has not been evaluated. We aimed to determine pooled rates, predictors and temporal-trend of VCE adverse events over the past two decades. Methods: Systematic search of PubMed and EMBASE for English-language publications reporting VCE adverse events (January 1, 2000 to March 31, 2019). Data were extracted independently by two investigators. Pooled VCE adverse event rates were calculated using the random or fix… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In a recent meta-analysis, the pooled adverse event rate for capsule retention was 0.26% (95% CI 0.00–0.77), whilst the procedural discomfort rate was 0.81% (95% CI 0.15–1.80). The authors also demonstrated that the CCE technical failure rate was 1.76% (95% CI 0.76–3.06) [ 47 ]. This was defined as equipment malfunction, recording gaps, short battery life duration, activation failure and inability to download images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, the pooled adverse event rate for capsule retention was 0.26% (95% CI 0.00–0.77), whilst the procedural discomfort rate was 0.81% (95% CI 0.15–1.80). The authors also demonstrated that the CCE technical failure rate was 1.76% (95% CI 0.76–3.06) [ 47 ]. This was defined as equipment malfunction, recording gaps, short battery life duration, activation failure and inability to download images.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic incomplete examination, defined as CCE not excreted or not reaching the rectum within the recording time, was 19.19% (95% CI 14.06–25.88) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians will have to consider the adverse events associated with PC, such as the impaction of the PC at the stenotic site or intestinal perforation within 33 hours. The SBCE retention rate is reported to be approximately 1% (74,79). If a hospital's retention rate is higher than 1%, the indications and contraindications of PC may need to be reconsidered.…”
Section: Proposed Algorithm For Sbce In Patients With Small Bowel Stenosismentioning
confidence: 99%
“…13 A limiting factor for this, however, is its availability and reliance on bowel preparation for complete and accurate imaging, when compared with longer-standing technologies, despite it being safe, more comfortable and acceptable to patients. 14,15 At present, reading a CCE recording is time-consuming and requires skilled and experienced readers. 16 Devices such as the PillCam COLON2 system from Medtronic record at a variable rate between 4 and 35 frames per second (fps) for a minimum of up to 10 hours, 17 thus providing hundreds of thousands of frames for review.…”
Section: Introductionmentioning
confidence: 99%